2020
DOI: 10.12968/gasn.2020.18.3.36
|View full text |Cite
|
Sign up to set email alerts
|

Regular clinical supervision to enhance wellbeing in inflammatory bowel disease specialist nurses: a small pilot study

Abstract: Background: Increasing demands oninflammatory bowel disease clinical nurse specialists (IBD-CNSs) can lead to overwhelming workloads, causing stress and burnout. Aim: To assess the potential for cognitive behavioural therapy (CBT)-based clinical supervision to enhance IBD-CNS wellbeing. Method: This exploratory qualitative study involved interviewing IBD-CNSs who had participated in CBT-based clinical supervision sessions delivered previously in one UK hospital by a psychotherapist. Interviews were audio-recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…An IBD-CNS collaborative workshop to acknowledge emotional impact and risk of burn-out identified that these specialist nurses need support addressing the many ways in which they are emotionally affected by their work, with an express request for further training and support, including access to clinical supervision 49. The potential for clinical supervision to counter burn-out in nurses is recognised50 51 and has been demonstrated, in principle, in one small pilot study with IBD-CNSs,52 but more work is needed to strengthen this evidence and to understand the experiences and implications of burn-out among these specialist nurses.…”
Section: Discussionmentioning
confidence: 99%
“…An IBD-CNS collaborative workshop to acknowledge emotional impact and risk of burn-out identified that these specialist nurses need support addressing the many ways in which they are emotionally affected by their work, with an express request for further training and support, including access to clinical supervision 49. The potential for clinical supervision to counter burn-out in nurses is recognised50 51 and has been demonstrated, in principle, in one small pilot study with IBD-CNSs,52 but more work is needed to strengthen this evidence and to understand the experiences and implications of burn-out among these specialist nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Such spaces have been eroded over time, with staff break rooms being non-existent or having multipurpose functions, 145 and some service architecture features make informal peer support challenging (eg, lone workers). [161][162][163]…”
Section: (Cmo12)mentioning
confidence: 99%
“…Unsurprisingly this included the well-reported staff shortages and high attrition in the professions [as reported above, within aim (a)], which could have knock on implications. For example, Lone working (N, 99,118,119 Poor relationships with colleagues/incivility/ bullying 9,25,30,34,75,83,89,90,96,110,123 Fear of assault/abuse from public/patients (P, 124 but also N and M in some settings e.g. emergency nurses, 23 secure forensic 25,111 ) Challenging relationships with patients, public, clients 23,80,100,105,106,111,124,125 Not feeling able to speak out 9,83,90,94,114 continued one nursing paper focused on newly qualified nurses 73 highlighted that this can mean regularly working with temporary staff (bank or agency staff) and/or being moved to other units (impacting teamwork and collegiality as well as knowledge of the systems and patients), and that such shortages can often mean being the only registered nurse on a shift, leading to feeling "vulnerable, and their units unsafe" 73 (p. 3).…”
Section: Demandsmentioning
confidence: 99%
“…Lone working was a specific (negative) feature of work mentioned in three nursing papers that focused on specific types of nurses [clinical nurse specialists for chronic conditions; 118 emergency nurse practitioners (ENPs) based in minor injuries units; 99 and children's community nurses based in rural or remote areas], 119 but this 'cause' is also relevant to any nurse, midwife or paramedic that works predominantly on their own (e.g. critical care paramedics who may spend most of their shift in a car on their own except for when attending incidents with other crews on scene; and nurses and midwives in rural/remote areas with a community caseload who may not often see their team members).…”
Section: Profession-specific 'Support' Causesmentioning
confidence: 99%
See 1 more Smart Citation